CONTENT OF MARKER CYTOKINES OF Th1- AND Th2-LYMPHOCYTES IN PERIPHERAL BLOOD AT ACUTE AND CHRONIC INFLAMMATION - Татарко С. В. (World of Medicine and Biology, 2014)
On different models of inflammation by etiology and course, an acute infectious, secondary chronic, primary chronic non-immune and primary chronic immune in rats, starting from the 6th hour and to 28th day after injection flogogen we investigated the content of marker cytokines of Th1-lymphocytes (IL-12, IFN-γ) and Th2-lymphocytes (IL-4). We showed that as chronization progresses there is a shift from the predominance of the activation of humoral immunity in acute inflammation, through its even more significant involvement in secondary chronic inflammation, in the direction of prevailing of cellular immunity activation in primary chronic inflammation.